Holocene hydroclimate reconstruction based on pollen, XRF, and grain-size analyses and its implications for past societies of the Korean Peninsula. (September 2021) - Park, Jinheum; Park, Jungjae; Yi, Sangheon; Lim, Jaesoo; Kim, Jin Cheul; Jin, Qiuhong; Choi, Jieun
The dynamics of the East Asian Summer Monsoon (EASM) and their link to past societies during the Holocene are topics of growing interest. In this study, we present results of pollen, geochemistry, and grain-size analyses from the STP18-03 core sampled from Miryang in the Korean Peninsula, which spans ca. 8.3–2.3 ka BP. In-phase relationships of these proxies revealed an imprint of the Holocene Climate Optimum (HCO) during the early to mid-Holocene and subsequent drying toward the late-Holocene in accordance with decreasing solar insolation. At centennial timescales, our study indicates drier climate during ca. 7.5–7.1, 6.4–6.0, and 4.8–3.6 ka BP. Notably, our finding for ca. 6.4–6.0 ka BP contributes further evidence of a drying event in the Korean Peninsula during this period. We suggest that the Pacific Ocean played a role in the underlying mechanism of hydroclimate change in the region. A strong Kuroshio Current (KC) and long-term El Niño–Southern Oscillation (ENSO)-like variability in the Western Tropical Pacific (WTP) were closely linked to the influence of the EASM over the Korean Peninsula. In particular, dry phases during ca. 4.8–3.6 and 2.8–2.3 ka BP, which were synchronous with a more active ENSO, closely corresponded to lower population levels indicated by a summed probability distribution (SPD) of archaeological records previously assembled in the Korean Peninsula. This finding implies that past human societies of Korea were highly vulnerable to climate deterioration caused by precipitation deficits.